2011
DOI: 10.1136/bjsm.2010.079244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of functional knee brace use on acceleration, agility, leg power and speed performance in healthy athletes

Abstract: An initial decrement in performance levels was recorded when a FKB is used during an alactic performance task. After 12.0-14.0 h of FKB use, performance measures were similar between the two testing conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
0
14
3
Order By: Relevance
“…An interesting and somewhat unexpected finding was that as the magnitude of constraint increased (no brace < Playmaker < TROM), peak knee flexion increased. Our results differed from the findings of Rishiraj et al., 30 who showed that acceleration, agility, leg power, and speed were all lower in male athletes wearing a custom-fitted functional knee brace. These differences, however, disappeared after 14 hours of brace use, suggesting acclimatization.…”
Section: Discussioncontrasting
confidence: 99%
“…An interesting and somewhat unexpected finding was that as the magnitude of constraint increased (no brace < Playmaker < TROM), peak knee flexion increased. Our results differed from the findings of Rishiraj et al., 30 who showed that acceleration, agility, leg power, and speed were all lower in male athletes wearing a custom-fitted functional knee brace. These differences, however, disappeared after 14 hours of brace use, suggesting acclimatization.…”
Section: Discussioncontrasting
confidence: 99%
“…After 14 hours of brace use, no differences in braced and non-braced groups were found, suggesting the need for an adaptation phase before engaging in full sport activity (24,25).…”
Section: Influence On Performancementioning
confidence: 94%
“…Athlete adjustment to the brace seems to be possible in terms of reaction, fatigue, and performance (23,24). After 14 hours of brace use, no differences in braced and non-braced groups were found, suggesting the need for an adaptation phase before engaging in full sport activity (24,25).…”
Section: Influence On Performancementioning
confidence: 99%
“…While FKBs are designed to be worn during activity, there is always a concern that its influence may negatively impact performance and agility. Yet, the work by Rishiraj et al 20 has shown that having worn braces for up to 12–14 h does not show performance deficits. However, the test condition utilized in our study was not challenging and the speed of movement was not high.…”
Section: Discussionmentioning
confidence: 97%